COVID-19-Associated Rhinocerebral Mucormycosis: An Increasingly Frequent Finding with Various Clinical Manifestations and Necessity for Critical Therapeutic Intervention - Andreescu, Mihaela; Mocanu, Horia; Mocanu, Adela-Ioana; Moldovan, Cosmin (Medical Science: Trends and Innovations Vol. 2, 2025)
Mucormycosis is a fatal infectious disease with associated high mortality rates. A significant body of evidence has emerged regarding the incidence of Mucormycosis in COVID-19 patients. With the advent of COVID-19, the number of patients diagnosed with mucormycosis has increased, especially in developing countries. The reason behind this increase is that COVID-19 causes hypoxia that promotes the growth of fungus. To identify the association between mucormycosis and COVID-19, in critically ill or immunocompromised COVID-19 patients. The literature included in the review was researched from October 1, 2021, to November 1, 2022, by using the Google Scholar database as the search engine. Of the 20 articles included, there were 4 case reports, 2 case series, 10 narrative reviews, and 4 quantitative studies. Mucormycosis, initially thought as an incidental finding in COVID-19 patients, has become a significant concern. Mucormycetes growth is caused by several factors, including hyperglycemia owing to previously existing diabetes or excessive use of steroids, increased ferritin levels owing to the inflammatory cascade initiated by COVID-19, and immunosuppression caused by the use of steroids or other immunosuppressive therapy. The dysregulation in the expression of ACE-2 in multiple organs can lead to suppression of the immune system and the development of a microenvironment that facilitates the growth of COVID-19. Reduced white cell count and activity in COVID-19 leads to increased germination of fungal spores hence developing a catastrophic picture of rhinocerebral mucormycosis. Considering that the hematological patient is frequently treated with cortisone, immunosuppressed due to the underlying condition, but also through the administered therapy, the association with possible diabetes makes this patient susceptible to developing rhinocerebral mucormycosis during COVID-19 infection. Despite being severe, the association between mucormycosis and COVID-19 is specific and treatable. Development of mucormycosis in hematological patients suffering from severe COVID-19 disease is dangerous, yet not compulsory and can be prevented. Using a common steroid-dose protocol with hyperbaric oxygen and necessary preventive measures reveals the disease as a superadded infection. As the review is systematic, an association between COVID-19 and mucormycosis could not be definitively established. Several predisposing factors occur that may lead to super-added mucormycosis in COVID-19 patients; therefore, further studies are required to evaluate histopathological and microbiological data to better understand the link between COVID-19 and mucormycosis.